Assessment of laboratory O4 (O2-O2 collision-induced) absorption cross-sections at 360 nm using atmospheric long-path DOAS observations - Lauster, Bianca; Frieß, Udo; Nasse, Jan-Marcus; Platt, Ulrich; Wagner, Thomas (Atmospheric measurement techniques, 2025)
Absorption of light in the atmosphere by collision-induced absorption (CIA) by two oxygen molecules O2-O2, in the following referred to as O4, can be used to derive properties of aerosols and clouds from remote sensing observations. In recent years, inconsistencies between the measured atmospheric O4 absorption and radiative transfer simulations were found for Multi-AXis Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements. In the presented study, over two years of observations from a long-path (LP-) DOAS instrument deployed at the German research station Neumayer, Antarctica, are analysed. While MAX-DOAS instruments measure spectra of scattered sunlight at different elevation angles, LP-DOAS utilises an artificial light source and the atmospheric absorptions are measured along a fixed (and well-defined) light path close to the surface. Further, the pristine measurement location allows one to investigate the relation between measured and modelled O4 absorption over a large range of temperatures (−45 to +5 °C). Overall good agreement is found between the retrieved O4 absorption cross-sections covering the absorption band at 360 nm and laboratory measurements. While the best agreement is obtained for the Finkenzeller and Volkamer (2022) cross-sections, deviations at cold ambient temperatures (below ca. −25 °C) are observed for the Thalman and Volkamer (2013) cross-sections. Other O4 absorption bands could not be investigated because these are not (fully) within the spectral range of the measured spectra. This study strongly supports the accuracy of commonly used O4 absorption cross-sections in DOAS analyses, while more work is needed to understand the earlier reported inconsistencies in MAX-DOAS observations.